Drivers of Family Planning Services Utilization in Pakistan: A Literature Survey and Recent Trends in Contraceptive Use - Urooj, Komal; Ahmad, Tusawar Iftikhar; Bhatti, Muhammad Azhar; Hussain, Altaf (iRASD Journal of Economics, 2022)
Population planning is inevitable for a sustainable and secure future of a lower middle-income economy, like, Pakistan which stands fifth populous economy across the globe and has high population growth rate. Based on Pakistan Demographic and Health Survey 2017-18 data and by covering a sample of 12339 ever-married females, the study intends to investigate the correlates of family planning services use in Pakistan as well as the use of contraceptives across the regions and districts of Pakistan. An exploration of 34 studies (spanning over a time from 1989 to 2021), specifically on Pakistan, with respect to family planning services utilization, have found that the use of family planning services was an outcome of a woman’s education, awareness status, wealth or economic status, religion, husband’s approval, area of residence, number of living children, prevalence of the desired family planning method, desire for more children, subsidized healthcare services and other social or individual factors. In Pakistan, the average contraceptive use rate was recorded as between 19-49 percent across the regions and between 0-71 percent across the districts. The region Islamabad Capital Territory (ICT) had the highest contraceptive usage rate, i.e., 49%, followed by: Punjab (42%), Khyber Pakhtunkhwa (KPK) and Gilgit Baltistan (39% each), Sindh and Azad Jammu and Kashmir (AJK) (34% each), Federally Administered Tribal Areas (FATA) (24%), and Balochistan (19%). Amongst the districts, top three districts with highest contraceptive usage were Jafarabad, Sheikhupura and Jhang whereas the districts of Rajanpur, Tor Ghar and Kohlu were lying at the bottom. Region-wise disaggregation found that in the province of Punjab and Sindh, the range of contraceptive use across the districts was respectively ranged between 0-70 percent and 8-60 percent. Likewise, in KPK and Balochistan provinces, the range of contraceptive use had been recorded between 0-59 percent and between 2-71 percent. While the range of contraceptive use in Gilgit-Baltistan, FATA region, and in AJK had been respectively recorded between 9-48 percent, 11-39 percent, and 17-47 percent.